Biophilic Design as A Strategy for Increasing The Quality of Spaces in Offices - Fatimah, D (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to describe the application of Biophilic Design Concept that can be applied in offices. A design based on the concept of biophilia, is called a biophilic design by presenting a green space to improve the quality of life that affects human health and physiological and psychological well-being. Biophilic design has had many positive outcomes, namely trying to reconnect humans and nature by providing all kinds of behavioral, mental, and physical benefits. This study aims to determine how appropriate the design criteria for designing offices with biophilic design theory are used. The method used is a qualitative descriptive method. First of all, the biophilic design concept will be explained. Then will be analysed the possible patterns that can be used in office design. Biophilic design has 14 patterns that can be realized through a direct or indirect relationship with nature. The essence of this biophilic design is to create a space in which there is interaction with nature which is a basic human need. Office areas can apply these 14 patterns into the design concept. Three basics concepts of Biophilic Design: nature in spaces, analogues of nature, and Nature of space can be applied to office design.